Pandemia COVID-19 e análise da conversa multimodal: porque o lar vira trabalho, mas o trabalho não vira um lar - Ohlweiler, Marina Kirsch (Universidade do Vale do Rio dos Sinos, 2022)
The COVID-19 pandemic, due to conditions of social distancing, led to a reconfiguration of the way of working (in person and working at home) of some Brazilian social groups. Employing Ethnomethodological and Multimodal Conversation Analysis, we analyzed interactions of two distinct family groups to understand how the social interactions of intimate and institutional life have been (co)constructed in the same spatial configuration (i.e., residences) during the pandemic period. The spatial configuration of the household was affected by the COVID-19 pandemic and shows two distinct domains. The first is composed of objects that represent institutional life (e.g., computer screen, cell phone, desk, dining table) and the latter, by objects related to intimate life (e.g., sofa, television, kitchen, bathroom). Nonetheless, domains are not only physical but also virtual. Moreover, their transition from one to another happens through a trigger/invitation, which marks a transition period, followed by the acceptance or refusal of the invitation to the new interactional context by the interactants. The expansion or retraction of domains depends on temporality and is the result of the interactants’ actions and decisions. We observed an asymmetry when there is an expansion of the domain of institutional life over the domain of intimate life. People have the agency to impose limits on the expansions and contractions of domains. However, the agency is limited by institutional proxies.
Keywords: Análise da conversa multimodal; Home office; Interação social; Pandemia COVID-19; Teletrabalho; COVID-19 pandemic; Multimodal conversation analysis; Social interaction; Work at home; ACCNPQ::Lingüística, Letras e Artes::Lingüística